IMPACTS OF IMPORT GROWTH ON THE DEVELOPMENT OF INDUSTRIAL SECTOR IN NIGERIA - Ahmed Oluwatobi ADEKUNLE (Malete Journal of Accounting and Finance, 2025)
The study was undertaken to find out the impact of import growth on the development of industrial sector in Nigeria. The study employed quantitative techniques over 1988 to 2023 using secondary sources of data from the central bank of Nigeria (CBN) were used. The findings show that imports have a significant positive relationship with industrial sector output. Furthermore, a significant relationship is shown between the exchange rate and industrial sector output, though positive and contrary to apriori expectation. The lag value of the dependent variable (indp (-1) is shown to have a significant positive relationship with industrial output. This also meets the apriori expectation. R2 shows a goodness of fit implying that the explanatory variables adequately explained the behavior of the dependent variables. the study recommends lower cost of importing vital raw materials for industries and the monetary authority should maintain exchange rate stability to prevent high price range to the final consumer.